Inflammatory markers detected in nasal lavage correlate with paranasal sinus abnormalities at MRI in adolescent patients with cystic fibrosis - Chung, Jaehi; Wünnemann, Felix; Salomon, Johanna J.; Boutin, Sébastien; Frey, Dario; Albrecht, Tobias; Joachim, Cornelia; Eichinger, Monika; Mall, Marcus A.; Wielpütz, Mark Oliver; Sommerburg, Olaf (Antioxidants, 2021)
Chronic rhinosinusitis (CRS) is a characteristic feature of cystic fibrosis (CF) multiorgan disease and develops early in the life of patients with CF. The study aimed to correlate the inflammatory markers and the presence of structural abnormalities detected by MRI in the paranasal sinuses of patients with CF. Methods: Nasal lavage and MRI of the paranasal sinuses was performed in a cohort of 30 CF patients (median age 14 y; range 7-20 y). Morphological abnormalities characteristic of CF were evaluated with a dedicated CRS MRI scoring system and correlated with different inflammation parameters measured in nasal lavage. Inflammation of the paranasal sinuses was positively associated with structural abnormalities in MRI. The concentration of the pro-inflammatory markers neutrophil elastase (NE) and the neutrophil elastase/alpha1-antitrypsin (NE/A1AT) complex correlated significantly with CRS-MRI sum score (p < 0.05, r = 0.416 and p < 0.05, r = 0.366, respectively). S. aureus infection was associated with the increased pro-inflammatory cytokine activity of IL-6 and IL-8, and increased levels of NE/A1AT complex in our patients (p < 0.05, respectively). CRS-MRI sum score and individual sinus MRI scores were positively associated with inflammatory activity as a sign of CRS pathology present in CF.
Gesehen am 22.02.2022